A Legal Analysis of Administrative Disputes Related to the Transfer of Civil Servants in the Makassar City Government - Ago, Muh. Syahrul; Mardatillah, Widya; Saodana, Shafira (Journal of Law, Politic and Humanities, 2025)
The transfer of positions among Civil Servants (PNS) has become one of the key issues in personnel governance and the implementation of the merit system in Indonesia. As a form of human resource (HR) management within the bureaucracy, transfers must be carried out based on the principles of administrative law, including the principles of legality, accountability, and propriety. However, in practice, transfers are often conducted in a non-transparent manner, not based on objective performance evaluations, and tend to be influenced by political interests or the subjectivity of staffing officials. Such practices have the potential to generate administrative disputes that lead to injustice for civil servants and undermine the principles of good governance. This research is important in filling the gap in the literature that specifically analyzes the transfer of civil servant positions from the perspective of administrative law. Most previous studies have focused on managerial or human resource policy aspects, but have not deeply examined the juridical dimensions that form the legal basis and validity of administrative decisions. Therefore, this study aims to examine two important aspects in the implementation process of civil servant transfers, particularly within the Makassar City Government: First, the legal foundations, procedures, and potential disputes arising from transfer decisions from an administrative law perspective. Second, the legal remedies available to civil servants within the Makassar City Government who feel aggrieved by such transfer decisions. Meanwhile, this study employs both normative and empirical juridical approaches. The normative approach is used to analyze relevant regulations such as Law No. 5 of 2014, Government Regulation No. 11 of 2017, as well as court decisions and opinions from supervisory institutions such as the Indonesian Ombudsman and the Civil Service Commission (KASN). The empirical approach, on the other hand, involves field studies and interviews with staffing officials, transferred civil servants, and other relevant stakeholders. This research seeks to provide a scientific contribution to strengthening the merit system, upholding administrative law principles within the bureaucracy, and serving as a foundation for the formulation of fairer, more transparent, and accountable policies.